A Comprehensive Study of Ecofeminism. (3rd October 2017) - Vijayaraj, Bhuvaneswari
ABSTRACT: Cartesian ontological belief has placed man over other beings and has separated humans from nature. This Cartesian hierarchical thinking has led to the destruction of the environment so much that our lives are at stake now. Man's anthropocentric behaviour has impelled him to a perilous situation where his very existence is threatened. Man's anthropocentric attitude is the root cause for this unprecedented climate change because the male supremacy believes that women as well as nature are entities that can be controlled. Ecofeminism, as a theory, challenges the existing patriarchal paradigms and holds that the there is a strong connection between women and nature and they are inseparable. The objective of this paper is to present a comprehensive view of ecofeminism as an emerging theory of literary research by focusing on its origin, development, precepts, and proponents.